MEKANISME SISTEM PENJAMINAN MUTU INTERNAL PERGURUAN TINGGI (Studi Kasus Pada Universitas Islam Balitar, Blitar) - Aspranawa, Anang Dwi Putransu; Pravitasari, Dyah (LP2M IAIN Tulungagung, 2018)
This research is a study that examines and describes the internal quality management system of higher education. Management system begins with activities planning, organizing, self-actualization and control. The Islamic Balitar University Blitar is carrying out internal quality assurance has been arranged integrally starting from education and teaching activities, until research activities and community services. The implementation quality of education itself is continuous improvement. This means that the Islamic Balitar University Blitar has established, implemented, evaluated the implementation, controlled the implementation and improve the quality standard of education run independently adjusted to the vision and mission of the college.Keywords: System, Management, Quality Assurance